PENGARUH ASAM VALPROAT TERHADAP PRESTASI BELAJAR ANAK DENGAN EPILEPSI - , Andrianto Selohandono ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background. Valproic acid is one of the AED commonly prescribed to control epileptic seizure. Cognitive and behavioral disorder have been associated with barbiturate and benzodiazepine, while their association with valproic acid is still a matter of debate. Valproic acid effect on academic performance in children with epilepsy is still largely unknown. Method. This is a case control study. Pediatric epileptic patient between 7-12 years old were recruited as subjects. Children who assigned with valproic acid were compared with children who received any non-valproic AED as control group. Academic performance were assessed from children report card, particularly their Indonesian language and math score compared their class average score. Result. A Total of 54 subjects were recruited for study, 22 subjects indicated worse academic performance in Indonesian language, while 30 subjects indicated worse academic performance in math. Generalized type seizure and the occurence of seizure in the last month were significantly and independently associated with worse academic performance. While, valproic acid only had significant associated with worse math performance in univariate analysis